PENGARUH KUALITAS KOMUNIKASI APARATUR SIPIL NEGARA TERHADAP KEPUASAN WAJIB PAJAK SISTEM ADMINISTRASI MANUNGGAL SATU ATAP PEKANBARU SELATAN - Lisa Naomy Nisa; Anuar Rasyid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The success of organizing public services is inseparable from the factors of communication and information by the government bureaucracy. One of the regional government bureaucracies in Riau Province that provides public services is the South Pekanbaru Samsat. Adequate communication and information aims to increase knowledge of taxpayers and ease of paying motor vehicle tax. The theory used in this study is the Laswell theory. The purpose of this study was to determine the taxpayer's response to the quality of communication of state civil apparatus, to determine the effect of the quality of communication of state civil apparatus on taxpayer satisfaction, and to analyze the influence of the quality of communication of state civil apparatus on taxpayer satisfaction.This study uses quantitative research methods with correlational research design using Simple Random Sampling and Slovin formulas, so this study obtained 98.99 people rounded up to 100 respondents. Researchers collected data through questionnaires, while for data analysis techniques researchers used correlation test techniques with simple linear regression formulas and statistical hypothesis tests.The results of this study indicate that the level of influence of communication quality on satisfaction of taxpayers in South Pekanbaru Samsat has a moderate effect. This is seen from simple linear regression in this study is Y = 8.911 + 0.757 X. Meanwhile t count 11.425 is greater when compared with t table of 1.984 with a significance level of 0.000 smaller than α = 0.05. Based on the table